Healthcare and Medical Apps : A Review - Jain, Deepak (Indian Journal of Computer Science, 2023)
Evolving technologies and mobile apps are revolutionizing the healthcare industry. These technologies overcome the traditional limitations of healthcare systems such as instant and secure access, accuracy, and mobility. Mobile devices and apps are proving beneficial for healthcare professionals, as they provide easy access to point-of-care tools, which enable better clinical decision-making and improved patient outcomes. The present paper reviews different types of technologies and mobile apps being used in the healthcare industry and their future potential.